Early loading after microfracturing of defects in the knee joint cartilage - Golovakha, Maksim (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2011)
Safety and efficacy of the use of early loading on the operated extremity after microfracturing of defects in the knee joint cartilages were analysed. The study involved 98 patients, aged from 28 to 58, with knee joint osteoarthrosis degrees I-II, who had been operated at least 3 years before. It is shown that the use of early loading on the operated extremity after microfracturing of process defects in the knee joint cartilages did not increase the level of postsurgical complications and did not produce any significant effect on remote results of the treatment versus the patients, whose extremities were unloaded after the operation.